CHARACTERISTICS AND RISKS IN THE APPLICATION OF ADJUVANTS IN AGRICULTURAL SPRAYING - Putti, F. F.; Gabriel Filho, L. R. A.; Bertin, F. H. A.; Cremasco, C. P.; Cataneo, P. F.; Chacur, M. G. M.; Halmeman, M. C. R.; Halmeman, R. J. (Revista Brasileira de Engenharia de Biossistemas, 2014)
There are several factors that influence effectiveness in the application of pesticides. They comprise relative humidity, wind speed and air temperature. The use of inert products, called adjuvants, has been on the increase to highlight efficiency in spraying under different aspects. Due to lack of knowledge of their activities, efficiency itself is often compromised by the interaction between adjuvants and phytosanitary products, with unintended consequences. Current study reviews some adjuvants and their mode of action, which may vary from an improvement in absorption by activity on the cuticle to the reduction of the iteration of ions of water and the active ingredient molecule. Since few studies on the use and effectiveness of adjuvants combined to specific pesticide formulations are extant, the use of adjuvants becomes a risky operation. Therefore, consulting specialized people who are familiar with the products and their possible interactions is mandatory before using or recommending the products. Loss of efficiency in phytosanitary control and environmental contamination may be thus avoided.